Genome‐wide association studies of response and side effects to the BNT162b2 vaccine in Italian healthcare workers: Increased antibody levels and side effects in carriers of the HLA‐A03:01 allele - Magri, Chiara; Marchina, Eleonora; Sansone, Emanuele; D'Adamo, Adamo Pio; Cappellani, Stefania; Bonfanti, Carlo; Terlenghi, Luigina; Biasiotto, Giorgio; Zanella, Isabella; Sala, Emma; Caruso, Arnaldo; Lombardo, Massimo; et al. (HLA, 2023)
The remarkable variability of response to vaccines against SARS‐CoV‐2 is apparent. The present study aims to estimate the extent to which the host genetic background contributes to this variability in terms of immune response and side effects following the administration of the BNT162b2 vaccine. We carried out a genome wide association study (GWAS) by genotyping 873 Italian healthcare workers who underwent anti‐SARS‐CoV‐2 vaccination with the BNT162b2 vaccine and for whom information about anti‐SARS‐CoV‐2 spike antibodies titers and vaccine side effects were available. The GWAS revealed a significant association between the HLA locus and the anti‐SARS‐CoV‐2 Spike antibodies level at 2 months following the first dose of vaccine (SNP: rs1737060; p = 9.80 × 10−11). In particular, we observed a positive association between the antibody levels and the presence of the HLA‐A*03:01 allele. The same allele was found associated with a 2–2.4‐fold increased risk of experiencing specific side effects such as fever, chills and myalgia and a 1.5–1.8‐fold increased risk of joint pain, nausea, fatigue, headache and asthenia, independently of age and sex. This study confirms that the heterogeneity in the immune response to the BNT162b2 vaccine and in its side effects are at least partially influenced by genetic variants. This information, integrated with individual biological and lifestyle‐related correlates, could be of use in the definition of algorithms aimed at the identification of subjects in which the administration of additional vaccine doses would be particularly beneficial to maintain immunity against the virus.